The Impact of Prenatal Perineal Massage on the Risk of Perineal Tears During Vaginal Childbirth - Elyana Aureen Anetha (Institute of Accounting Research and Novation (IARN), 2026)
Perineal trauma is one of the most common complications experienced by women during vaginal childbirth. A Perineal Tear can cause several short-term and long-term maternal health problems, including pain, infection, postpartum hemorrhage, and dyspareunia. One non-invasive intervention that has gained increasing attention in maternal health care is Perineal Massage, which aims to increase the elasticity and flexibility of the perineal tissues and prepare them for the stretching that occurs during childbirth. This study aims to examine the impact of prenatal perineal massage on the risk of perineal tears during vaginal delivery. This study used a quasi-experimental design involving pregnant women in their third trimester who planned to deliver vaginally. Participants were divided into an intervention group and a control group. The intervention group performed prenatal perineal massage starting from 34–36 weeks of gestation with a frequency of three to four times per week, while the control group received routine prenatal care without the massage intervention. Data were collected through direct observation during childbirth and review of medical records to identify the incidence and severity of perineal tears. The results showed that the incidence of perineal tears was lower in the intervention group compared with the control group. Women who performed prenatal perineal massage experienced fewer and less severe tears, and a higher proportion maintained an intact perineum during delivery. Statistical analysis using the Chi-square test showed a significant difference between the two groups (p < 0.05). These findings suggest that prenatal perineal massage is a simple and effective intervention to reduce perineal trauma and improve maternal health outcomes during vaginal childbirth.